FIGURE-OF-EIGHT BANDAGING TECHNIQUE EFFECTS ON GAIT AND BALANCE OF NEUROLOGICAL PATIENTS: SISTEMATIC REVIEW - Santos, Alan Carlos Nery dos; Almeida, Laize Pacheco dos Santos; Barbosa, Juliana Eletícia Silva; Cerqueira, Laís Sena Silva; Oliveira, Mariana Pereira de; Mota, Renata de Sousa (Manual Therapy, Posturology & Rehabilitation Journal, 2017)
Introduction: patients with common neurological diseases among others, there is no balance and gait, the reason that leads to functional decline and quality of life. Objective: To review the effects of bandaging in any treatment of gait and balance of individuals affected by neurological diseases. Methods: A study was carried out in the databases SCHOLAR GOOGLE, EBSCO, LILACS, SCIELO, PUBMED and MEDLINE, using the following descriptors: Gait; Orthotic devices; Postural Balance and Neuromuscular Diseases. As researches were conducted between July and December 2016, having as criteria: studies with adult neurological patients, which are the effects of bandaging in our nodes of gait, balances and functionality of the population. The studies were initially screened by title and abstract. In all the studies that fit the selection criteria were retrieved for reading in the integration, evaluation of the methodological quality and extraction of the data of interest for the review. Results: As database queries resulted in the identification and selection of four studies. Three of them were developed with volunteers patients affected by stroke. Both studies had the effect of the acute bandaging in eight. However, as analyzed variables ranged between static and dynamic equilibrium, gait and functionality. Only three references obtained significant results. The main results indicate the improvement of walking speed, the activation of the anterior tibial muscle, functional mobility and the balance of the evaluated population. Conclusion: The results of this review show that the figure-of-eight bandaging technique promotes significant improvement in clinical gait variables, static and dynamic balance.